Brief school‐based interventions and behavioural outcomes for substance‐using adolescents - Carney, Tara (Cochrane Database Syst Rev, 2016)
BACKGROUND: Adolescent substance use is a major problem in and of itself, and because it acts as a risk factor for other problem behaviours. As substance use during adolescence can lead to adverse and often long‐term health and social consequences, it is important to intervene early in order to prevent progression to more severe problems. Brief interventions have been shown to reduce problematic substance use among adolescents and are especially useful for individuals who have moderately risky patterns of substance use. Such interventions can be conducted in school settings. This review set out to evaluate the effectiveness of brief school‐based interventions for adolescent substance use. OBJECTIVES: To evaluate the effectiveness of brief school‐based interventions in reducing substance use and other behavioural outcomes among adolescents compared to another intervention or assessment‐only conditions. SEARCH METHODS: We conducted the original literature search in March 2013 and performed the search update to February 2015. For both review stages (original and update), we searched 10 electronic databases and six websites on evidence‐based interventions, and the reference lists of included studies and reviews, from 1966 to February 2015. We also contacted authors and organisations to identify any additional studies. SELECTION CRITERIA: We included randomised controlled trials that evaluated the effects of brief school‐based interventions for substance‐using adolescents. The primary outcomes were reduction or cessation of substance use. The secondary outcomes were engagement in criminal activity and engagement in delinquent or problem behaviours related to substance use. DATA COLLECTION AND ANALYSIS: We used the standard methodological procedures outlined by The Cochrane Collaboration, including the GRADE approach for evaluating the quality of evidence. MAIN RESULTS: We included six trials with 1176 adolescents that measured outcomes at different follow‐up periods in this review. Three studies with 732 adolescents compared brief interventions (Bls) with information provision only, and three studies with 444 adolescents compared Bls with assessment only. Reasons for downgrading the quality of evidence included risk of bias of the included studies, imprecision, and inconsistency. For outcomes that concern substance abuse, the retrieved studies only assessed alcohol and cannabis. We generally found moderate‐quality evidence that, compared to information provision only, BIs did not have a significant effect on any of the substance use outcomes at short‐, medium‐, or long‐term follow‐up. They also did not have a significant effect on delinquent‐type behaviour outcomes among adolescents. When compared to assessment‐only controls, we found low‐ or very low‐quality evidence that BIs reduced cannabis frequency at short‐term follow‐up in one study (standardised mean difference (SMD) ‐0.83; 95% confidence interval (CI) ‐1.14 to ‐0.53, n = 269). BIs also significantly reduced frequency of alcohol use (SMD ‐0.91; 95% CI ‐1.21 to ‐0.61, n = 242), alcohol abuse (SMD ‐0.38; 95% CI ‐0.7 to ‐0.07, n = 190) and dependence (SMD ‐0.58; 95% CI ‐0.9 to ‐0.26, n = 190), and cannabis abuse (SMD ‐0.34; 95% CI ‐0.65 to ‐0.02, n = 190) at medium‐term follow‐up in one study. At long‐term follow‐up, BIs also reduced alcohol abuse (SMD ‐0.72; 95% CI ‐1.05 to ‐0.40, n = 181), cannabis frequency (SMD ‐0.56; 95% CI ‐0.75 to ‐0.36, n = 181), abuse (SMD ‐0.62; 95% CI ‐0.95 to ‐0.29, n = 181), and dependence (SMD ‐0.96; 95% CI ‐1.30 to ‐0.63, n = 181) in one study. However, the evidence from studies that compared brief interventions to assessment‐only conditions was generally of low quality. Brief interventions also had mixed effects on adolescents' delinquent or problem behaviours, although the effect at long‐term follow‐up on these outcomes in the assessment‐only comparison was significant (SMD ‐0.78; 95% CI ‐1.11 to ‐0.45). AUTHORS' CONCLUSIONS: We found low‐ or very low‐quality evidence that brief school‐based interventions may be more effective in reducing alcohol and cannabis use than the assessment‐only condition and that these reductions were sustained at long‐term follow‐up. We found moderate‐quality evidence that, when compared to information provision, brief interventions probably did not have a significant effect on substance use outcomes. It is premature to make definitive statements about the effectiveness of brief school‐based interventions for reducing adolescent substance use. Further high‐quality studies examining the relative effectiveness of BIs for substance use and other problem behaviours need to be conducted, particularly in low‐ and middle‐income countries.